(untitled) (Journal of Engineering, 2013)
Theoretical and experimental investigations of the transient heat transfer parameters of constant heat flux source subjected to water flowing in the downward direction in closed channel are conducted. The power increase transient is ensured by step change increase in the heat source power. The theoretical investigation involved a mathematical modeling for axially symmetric, simultaneously developing laminar water flow in a vertical annulus. The mathematical model is based on one dimensional downward flow. The boundary conditions of the studied case are based on adiabatic outer wall, while the inner wall is subjected to a constant heat flux. The heat & mass balance equation derived for specified element of bulk water within the annulus and solved by using Laplace method to determine the variation of bulk water temperature. The experimental investigation included a set of experiments carried out to investigate the temperature variation along the heat source for power increase transient of (5%, 10%, 15% and 20%) of its nominal value during and after reaching the steady state condition. Estimation of the boiling safety factor is predicted and compared with the theoretical values. Reliable agreement between experimental and theoretical approaches is reached. The later showed that the elapsed time required for the clad surface temperature to reach its steady state values after each transient is less than that related to bulk water temperature. New correlation for prediction of critical heat flux, CHF based on inlet water temperature and water mass flux are investigated and compared with CHF correlations obtained from previous researches. Specific recommendations concerned with preventive measured required to eliminate the effect of boiling crisis are concluded based on theoretical and experimental results related to transients setting times obtained from each case study.